E-booklet Sebagai Media Informasi Mengenai Fenomena Cancel Culture di Media Sosial - Rahmanida, Syifa; Hidayatullah, Taufan (Fakultas Desain Universitas Komputer Indonesia, 2023)
Cancel culture is a phenomenon where someone will be eliminated because they are considered to have made a mistake either intentionally or unintentionally and are also considered offensive or problematic. This phenomenon is growing in Indonesia and can be found anywhere, but the cancel culture phenomenon is more common on social media because social media is free to express their opinions on something. cancel culture occurs as a form of protest and dislike for people, especially celebrities, who are considered to be against social norms. And this phenomenon is often misdirected, causing an impact on its victims for the hate speech they receive. But unfortunately there are still many people who do not know about this culture. So an information media design is needed as an effort to provide insight into the culture. Especially considering that there is still a lack of information media that discusses cancel culture, especially printed media. Based on this, the design of information media about the cancel culture phenomenon in the realm of social media will be made in the form of an illustrated e-booklet with various interesting visuals.